2006
DOI: 10.1111/j.1439-0310.2005.01187.x
|View full text |Cite
|
Sign up to set email alerts
|

Brood Parasitism and Nest Takeover in Common Eiders

Abstract: Conspecific brood parasitism (CBP) is an alternative breeding tactic that occurs in many brood‐tending animals and can have important fitness effects for both host and parasite. We use protein fingerprinting of egg albumen to distinguish the eggs from different females and to estimate the frequency, pattern and tactics of CBP and other forms of mixed maternity in a Hudson Bay population of common eiders (Somateria mollissima sedentaria). Mixed clutches, containing eggs from more than one female, occurred in 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 53 publications
6
45
1
Order By: Relevance
“…To avoid increasing the risk of predation we always covered the clutch with debris or down after handling (Go¨tmark and Å hlund 1984), and so did most females when leaving the nest. Conspecific brood parasitism is common in this population, and an estimated 20-42% of the nests were parasitised in studies by Robertson (1998) and Waldeck and Andersson (2006). We identified parasitic eggs by protein fingerprinting and laying patterns (Andersson and Å hlund 2001); they are not included in clutch sizes here.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…To avoid increasing the risk of predation we always covered the clutch with debris or down after handling (Go¨tmark and Å hlund 1984), and so did most females when leaving the nest. Conspecific brood parasitism is common in this population, and an estimated 20-42% of the nests were parasitised in studies by Robertson (1998) and Waldeck and Andersson (2006). We identified parasitic eggs by protein fingerprinting and laying patterns (Andersson and Å hlund 2001); they are not included in clutch sizes here.…”
Section: Methodsmentioning
confidence: 98%
“…We identified parasitic eggs by protein fingerprinting and laying patterns (Andersson and Å hlund 2001); they are not included in clutch sizes here. In 11 cases, after a female laid a first egg, the nest was taken over by another female who continued laying in it (Waldeck and Andersson 2006). All eggs from these nests are included in calculations of nest predation.…”
Section: Methodsmentioning
confidence: 99%
“…Both nests from which eggs were taken were deserted 24 h later. Females repeatedly experiencing gull attacks also risk injury (see Waldeck and Andersson 2006), and may be more prone to desert after egg predation than females that simply miss an egg upon returning.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually similar in size to the next two eggs in the clutch, whereas later eggs are progressively smaller (e.g. Swennen and Van der Meer 1992;Waldeck and Andersson 2006). Schamber et al (2008) tested several predictors of body fat reserves in Wve species of waterfowl and found that body mass alone is a suitable simple condition index.…”
Section: Methodsmentioning
confidence: 99%
“…Females that strive to nest early may be those which wish to avoid parasitic egg laying (Waldeck and Andersson 2006) which is common at Rif, particularly in the rock island (Kristjánsson and Jónsson 2015). Interestingly, the rock island generally initiated nesting 4-11 days earlier but also had a higher occurrence of clutches with 7 eggs or higher (32.4-17.3 % in 2012, the authors, unpublished data).…”
Section: Which Individuals Are the First Nesters?mentioning
confidence: 99%